PENGARUH KUALITAS LAYANAN,KUALITAS PRODUK,PERSEPSI HARGA,LOKASI TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi Pada Warung SPESIAL SAMBAL(SS) Di Sampangan Semarang) - Khoirul Muttaqin, 14.05.51.0153; Maskur, Ali (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of service quality, product quality, price and location perceptions on customer satisfaction and its impact on customer loyalty at Waroeng Spesial Sambal. The population in this study were customers at Waroeng Spesial Sambal. The sampling technique uses purposive sampling. The sample criteria in this study are customers who have already purchased more than 3 times at Waroeng Spesial Sambal. The analytical tool used is multiple linear regression. The results of the study can be concluded that: Service Quality has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction. Price perception has no significant effect on customer satisfaction. Location has no significant effect on customer satisfaction and customer satisfaction has a positive and significant effect on customer loyalty.